Study on optimization of coagulation-flocculation of fish market wastewater using bittern coagulant – response surface methodological approach. (22nd April 2022) - Bagastyo, Arseto Yekti; Anggrainy, Anita Dwi; Gatneh, Syaima; Nurhayati, Ervin; Susanti, Diah; Widodo, Erwin; Soehartanto, Totok; Warmadewanthi, IDAA
Abstract: Bittern contains a high ionic strength that can be used as an alternative coagulant in wastewater treatment. The magnesium content in the bittern could promote the removal of suspended particles and nutrients as settleable precipitates. This would create a more compact and manageable sludge. This study investigates the performance of bittern as a coagulant for fish market wastewater treatment. The effectiveness of bittern was evaluated based on the efficiency of pollutants removal and the amount of residual magnesium. The experiments were performed using a standard jar test. Response surface methodology (RSM) based on a two-factor central composite design (CCD) was used to design the experiment. The parameters involved were pH (7.5, 9, and 10.5) and coagulant dose (0.5, 1.5, 2.5 mL L −1 ). The maximum removal efficiencies (i.e., 93.3% TSS, 87.5% COD, 37.6% ammonium, and 91.3% phosphate) were recorded at pH 10.5 and 1.5 mL L −1 dose of bittern, while the optimum results (desirability value of 0.929) may occur at pH 10.5 and a dose of 1.284 mL L −1 . Approximately 51% of struvite and 48% of calcite precipitates were identified in the generated sludge, which can possibly be used as supplementary material in agrochemical industry with further treatment. HIGHLIGHTS: Central composite design (CCD) was used to develop the design of experiments. The highest removal of ammonium and phosphate by bittern coagulant was 37.6% and 91.3%, respectively. The selected optimum scenario suggests that coagulant dose of 1.284 mL −1 at pH 10.5 may remove 78% TSS, 84% COD, 36% ammonium, and 89% phosphate with Mg residual of 1, 383 mgL −1 .